Strain rate effects on the compressive response of wood and energy absorption capabilities – Part A: Experimental investigations. (1st August 2016) - Wouts, J.; Haugou, G.; Oudjene, M.; Coutellier, D.; Morvan, H.
Abstract: Strain rate effect on wood material is of major interest when dealing with applications dedicated to energy absorption or wood machining. To understand and evaluate the strain rate influence on the wood responses, three experimental apparatus are used in order to cover a large range of strain rates, between 0.001 and 600 s - 1, and to allow observing densification regime for strains until 70%. The influence of strain rate on mechanical properties, in particular, initial crushing stress, plateau stress and specific absorbed energies is investigated in the three orthotropic directions for two wood species (spruce and beech) really different in terms of relative density and microstructure. It is noticed that wood properties are strain rate sensitive and this sensitivity depends on the loading direction.